Effect of the Addition of Tapioca Flour and Moringa Leaf Puree (Moringa oleifera) on Proximate Analysis of Shellfish Siomay - Nurun Nafiah, Nisa; Finatsiyatull Rosida, Dedin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Moringa leaf puree is rich in amino acids, making it a valuable nutritional ingredient, while tapioca flour, due to its amylose and amylopectin content, enhances the chewiness of food products. Mollusks, particularly clams and snails, are excellent sources of protein and minerals. This study aimed to evaluate the effects of tapioca flour and moringa leaf puree addition on the nutritional composition of siomay made from shellfish. A randomized block design with two factors was employed: (1) the type of shellfish (blood clam, green clam, and rice snail) and (2) the proportion of tapioca flour to moringa leaf puree (50:50, 75:25, and 100:0). The best formulation was obtained from siomay made with rice snail and a tapioca flour-to-moringa puree ratio of 75:25, yielding a moisture content of 50.14%, ash content of 5.6%, fat content of 2.82%, protein content of 9.84%, and carbohydrate content of 31.60%. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero Hunger. SDG 3: Good Health and Well-being. SDG 12: Responsible Consumption and Production. SDG 14: Life Below Water